The bishop eaudiobook Bowers files series, book 4. - James, Steven (Patrick Bowers Files, 2010)
Gold Medallion and Christy Award nominee Steven James crafts pulse-pounding psychological thrillers that hold listeners spellbound. This fourth in his CBA bestselling series pushes FBI Special Agent Patrick Bowers' cutting-edge skills to the limit when a woman is found brutally murdered near Washington, D.C. While her killers continue a spree of perfect crimes, Bowers struggles to discover a pattern and crack his most difficult case yet.